417 Limited fluid and restricted toileting are associated with reduced work productivity in women at work. (24th April 2018) - Pierce, Heather; Perry, Lin; Gallagher, Robyn; Chiarelli, Pauline
Abstract : Introduction: Occupational demands influence workers' fluid intake and toileting behaviours. Access to fluids and toilets is necessary for bladder health and effective management of storage urinary symtoms, including urinary frequency, urgency and incontinence. These conditions are prevalent in women, yet little is known of the relationship between fluid intake, toileting and work productivity for those with storage urinary symptoms at work. Methods: A survey was distributed to 600 female nurses and midwives at three urban hospitals between June and November 2016. Logistic modelling was used to estimate the predictive association between limited fluid intake, restricted toileting and work impairment for those with storage urinary symptoms at work. A modified version of the Work Limitations Questionaire was used to measure time management, mental concentration and physical demands. We adjusted the model for age, body mass index, back pain, anxiety, depression, storage urinary symptoms at any time (not just at work) and other pelvic floor dysfunctions. Results: Of the included sample (n=353), 77.1% (95% CI: 73 to 81) delayed voiding at work, 22.4% (95% CI: 18 to 27) could not access the toilet when required, and 26.9% (95% CI: 22 to 32) reduced fluid intake to delay or avoid voiding at work. Almost half of the sample (46.7%; 95% CI: 42 to 52) reported storage urinary symptoms at work: those who limited fluids were more likely to have time management work impairment than those who didn't (OR: 3.87; 95% CI: 1.63 to 9.15). Those who delayed voiding were more likely to have concentration impairment than those who didn't (OR: 8.38; 95% CI: 1.03 to 68.45). Discussion: A worker's capacity to access fluids and toilets at work is modifiable, hence associated urinary symptoms and productivity loss may be preventable. Occupation-specific barriers to healthy bladder behaviours should be identified and redressed. Bladder health promotion should be considered for inclusion in occupational health programs.